Urban Walks and Visual Exploration - Lutfi, Dina (Journal of Posthumanism, 2025)
This article is about exploring everyday life within a city— specifically the city of Al-Khobar in Saudi Arabia. My exploration is one of urban identity, space, and the visual communication that can be found within urban public spaces. The aim, through qualitative research, is to observe and better understand the position of city inhabitants through the lens of being a resident, but also a designer navigating its spaces. The visual aspects of this study show parts of the city encountered over time to visually interpret quotidian elements. The city is eclectic, and the visual documentation in this article includes photography, illustrations, and mixed media. The representation of micro and macro details of cities is a way to familiarize the reader and viewer with what can be experienced in but is sometimes too familiar to recognize. It also aims to encourage those interested in urban environments to think about how we shape our cities and are simultaneously shaped by them. City spaces can be similar and different around the world; it is the personal encounter and symbiotic relationships between objects, memories, and actions that add connotative layers to urban spaces.